Cancer risk in patients with hepatitis C virus infection: a population‐based study in Sweden. (4th April 2017) - Liu, Xiangdong; Chen, Yanqing; Wang, Youxin; Dong, Xiaohua; Wang, Junming; Tang, Jianhua; Sundquist, Kristina; Sundquist, Jan; Ji, Jianguang
Abstract: Increased risks of certain cancers have been observed in patients with hepatitis C virus (HCV) infection. However, data on other cancer sites/types are lacking. We analyzed systematically the risk of developing 35 common cancers in patients with HCV infection using a nationwide Swedish database. Patients with HCV infection were identified from the Swedish Hospital Inpatient and Outpatient Register and Primary Health Care Database, and followed until the diagnosis of cancer. Standardized incidence ratios (SIRs) were calculated for subsequent 35 common cancer sites/types between 1990 and 2010 in patients with HCV infection in Sweden. Increased risks were recorded for six cancers. The highest SIR was seen for liver cancer (36.67; 95% CI: 33.20–40.40). The decreased risk was for prostate cancer (0.73; 95% CI: 0.59–0.90) and melanoma (0.50; 95% CI: 0.30–0.79). A significant sex‐difference for cancer was observed only for liver cancer (40.72; 95% CI: 36.36–45.45 for men and 27.21; 95% CI: 21.90–33.41 for women). Also, increased SIRs were noted only for liver cancer during the entire period of follow‐up. HCV infection was associated with an increased incidence of liver cancer and additionally five other types of cancer. Active surveillance of other cancers may be needed in order to be diagnosed at an earlier stage. Abstract : HCV infection was associated an increased incidence of liver cancer and additionally five other types of cancer. Active surveillance of other cancers may be needed in order to be diagnosed at an earlier stage.